If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y-1=(3/4)y+9
We move all terms to the left:
2y-1-((3/4)y+9)=0
Domain of the equation: 4)y+9)!=0We add all the numbers together, and all the variables
y!=0/1
y!=0
y∈R
2y-((+3/4)y+9)-1=0
We multiply all the terms by the denominator
2y*4)y+9)-((-1*4)y+9)+3=0
We add all the numbers together, and all the variables
2y*4)y+9)-((-4)y+9)+3=0
Wy multiply elements
8y^2-4)y+9)+3=0
| -98=2(-6n-7) | | (10y+10)+(4y+2)=180 | | 10−2j=–3j | | 84z=180 | | 1x+8=4(x+2 | | 5q=2q-2+q | | 1/3 (6+9x)=14 | | -6a+11=35 | | 4x+2=74° | | -2(5x+6)=2(-5x+5) | | (10y+10)+(4y-2)=180 | | 12x-15=392x+30 | | (2.3x+2.8)=(1.2x+9.8) | | -1/3+2/3m=2/3m-2/3 | | b+3/5=-3 | | 3(15x+15)=180 | | 4x+2=740 | | 31 (6+9x)=14 | | 1x+4=3(x+2) | | 99-4x=111 | | 5/2k+1-14/3k=-5/8 | | -3(4x+1)=5(-6x+7)-2 | | 3x-4/8=2x-3/6 | | K+6m=8 | | 2/5(g-)=3 | | 35+4x=7x+7*5 | | 1/6(12m-18)=2m-3 | | 0.6x+64.26=264 | | (x−4)2=28 | | 5)-14+6b+7-2b=1+5b | | x^2-x-20=x^2-3x | | 1/2x-20=10 |